Perspectives on sexual history taking in routine primary care consultations in North West, South Africa: Disconnect between patients and doctors - Deidré Pretorius; Motlatso G. Mlambo; Ian D. Couper (AOSIS, 2022)
Background: Sexual history is rarely taken in routine consultations and research reported on common barriers that doctors experience, such as gender, age and cultural differences. This article focuses on how patients and doctors view sexual history taking during a consultation and their perspectives on barriers to and facilitators of sexual history taking. Aim: This study aimed to explore doctors' and patients' perspectives on sexual history taking during routine primary care consultations with patients at risk of sexual dysfunction. Setting: The research was conducted in primary care facilities in the Dr Kenneth Kaunda Health District, North West province. Methods: This was part of grounded theory research, involving 151 adult patients living with hypertension and diabetes and 21 doctors they consulted. Following recording of routine consultations, open-ended questions on the demographic questionnaire and brief interactions with patients and doctors were documented and analysed using open inductive coding. The code matrix and relations browsers in MaxQDA software were used. Results: There was a disconnect between patients and doctors regarding their expectations on initiating the discussion on sexual challenges and relational and clinical priorities in the consultation. Patients wanted a doctor who listens. Doctors wanted patients to tell them about sexual dysfunction. Other minor barriers included gender, age and cultural differences and time constraints. Conclusion: A disconnect between patients and doctors caused by the doctors' perceived clinical priorities and screening expectations inhibited sexual history taking in a routine consultation in primary care.